Graphene field-effect transistors for high frequency and flexible electronics - Krivic, Marijana (My University, 2019)
Graphene field-effect transistors (GFETs), owing to graphene’s intrinsically high velocity of charge carriers in combination with flexibility, are considered as key components for development of the new generation of advanced electronics for applications in the areas of high data rate communication, high-resolution sensors, imaging etc. It is well recognised now, that the development of GFETs, operating in the amplifying mode, is challenging due to relatively high differential drain conductance, resulting from the zero energy bandgap in the monolayer graphene, which prevents the drain current saturation and, hence, limits the transistor power gain. However, there is an additional possible effect of the high drain conductance in GFETs – the correspondingly high dissipating power which can result in additional degradation of the transistor high frequency performance due to Joule heating, i.e. self-heating, which is particularly pronounced in GFETs on polymer flexible substrates with inherently low thermal conductivity. This effect has been insufficiently addressed so far. The objectives of this Master’s thesis are both theoretical and experimental study of the GFET self-heating, its effect on the transistor high frequency performance and optimisation of the transistor design with the aim to reduce the self-heating. In this work, GFETs on rigid (Si/SiO2) and flexible polymer (Kapton) substrates have been designed, fabricated and characterised. The key issues of fabrication of GFETs on flexible substrates, e.g. misalignment during e-beam lithography, have been identified, discussed and addressed. A number of thermal resistance models allowing for evaluation of the GFET channel temperature defined by the selfheating have been considered. The models appropriate for certain GFET layouts and layered structure, on both Si/SiO2 and Kapton substrates, have been selected and applied. This allowed for considering GFET design optimisation for lower thermal resistance with the aim to reduce the self-heating effect. The actual GFET channel temperature has been measured by the means of infrared imaging and applying method of the thermo-sensitive electrical parameters, i.e. gate and drain currents, which showed a good agreement with the modelling. Finally, the effect of the self-heating on the high frequency performance of the fabricated devices has been analysed.
Keywords: graphene field-effect transistors; Joule heating; self-heating; thermal resistance; high frequency electronics; flexible electronics; infrared imaging; thermo-sensitive electrical parameters